2012
DOI: 10.1111/j.1574-6941.12000.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-specific C/N relative use efficiency for amino acids in an estuarine community

Abstract: Microbial activity plays a critical role in determining the nutrient status of an ecosystem (i.e. N or C limitation). While the balance of C/N assimilation has been measured at the whole community scale, quantitative detection of N and C assimilation from a single substrate at the scale of individual taxa has not been carried out. We recently developed Chip-SIP, a microarray and NanoSIMS-based method for linking microbial phylogeny and function that allows simultaneous measurement of (15)N and (13)C incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…Bacteria were enriched in both 13 C and 15 N after incubation with the dual-labeled amino acids, consistent with previous studies (e.g., Mayali et al, 2013). But, in the same incubations, only 15% of the Thaumarchaeal cells enriched in 15 N were also enriched in 13 C. This demonstrates that although they were active, most of the Thaumarchaeota cells did not assimilate carbon from amino acids.…”
Section: Carbon Metabolism Of the Thaumarchaeota Assessed By Fish-nansupporting
confidence: 91%
“…Bacteria were enriched in both 13 C and 15 N after incubation with the dual-labeled amino acids, consistent with previous studies (e.g., Mayali et al, 2013). But, in the same incubations, only 15% of the Thaumarchaeal cells enriched in 15 N were also enriched in 13 C. This demonstrates that although they were active, most of the Thaumarchaeota cells did not assimilate carbon from amino acids.…”
Section: Carbon Metabolism Of the Thaumarchaeota Assessed By Fish-nansupporting
confidence: 91%
“…This result casts doubt on the use of bacterial production estimates, which are largely based on uptake of leucine or thymidine. Following up on that work, Mayali et al (2013) found further evidence of taxon-specific uptake of amino acids in an estuarine system. Additionally, they discovered that Roseobacters incorporated relatively more N and Bacteroidetes relatively more C from an amino acid mixture, potentially because they are selectively incorporating specific components of the mixture.…”
Section: Amino Acidsmentioning
confidence: 92%
“…This work advances a quantitative approach to stable isotope probing in order to elucidate taxon-specific processes that drive element cycling in intact communities, bringing to microbial ecology the power of stable isotopes to quantify rates of element fluxes into and through organisms (65,66). Like Chip-SIP (48,67), qSIP provides a means to quantify the ecology of organisms about which we know little more than the genetic fragment used to identify their unique place on the tree of life. These approaches lay the groundwork for a quantitative understanding of microbial ecosystems, including the types of ecological interactions previously described among macroorganisms that influence ecosystem processes.…”
Section: Discussionmentioning
confidence: 99%